2017
DOI: 10.1002/2015jd024626
|View full text |Cite
|
Sign up to set email alerts
|

The effect of moisture source and synoptic conditions on precipitation isotopes in arid central Asia

Abstract: The stable isotope composition of precipitation has been widely applied to trace moisture sources. In the westerly dominated areas of central Asia, the isotopic composition of precipitation significantly correlates with surface air temperature, and the temperature effect is widely accepted. However, the significance of isotopes in tracing water vapor source is not clear for this region, and a further investigation using event‐based observations is still needed. Based on a network around the Tianshan Mountains,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
59
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 91 publications
(72 citation statements)
references
References 55 publications
2
59
0
Order By: Relevance
“…This seasonal change is similar to that of temperature, reflecting continental climate characteristics [27]. Terrestrial moisture evaporated from Europe and central Asia may be the main moisture source around the Tianshan Mountains [28].…”
Section: Introductionmentioning
confidence: 59%
“…This seasonal change is similar to that of temperature, reflecting continental climate characteristics [27]. Terrestrial moisture evaporated from Europe and central Asia may be the main moisture source around the Tianshan Mountains [28].…”
Section: Introductionmentioning
confidence: 59%
“…An interesting feature is found that the ice‐melt water is generally more enriched in heavy isotopes than the summer precipitation in the SETP, while it is inverse in the Tianshan Mountains. This is probably due to lack of monsoon sources for precipitation in the Tianshan Mountains (Kong & Pang, ; Li et al, ; Wang et al, , ), which is beyond the discussion of this work.…”
Section: Resultsmentioning
confidence: 92%
“…Winter precipitation in this region is very limited, and amount‐weighted precipitation isotope ratios are higher than the tap water values on an annual basis (Figures a and b). Tap water in this region is also characterized by limited seasonal isotopic variability (Figure S5a), despite large variations in precipitation isotope ratios (Wang et al, ; Zhang & Wang, , ), leading to the largest observed seasonal offsets between tap water and precipitation (Figure a). This argues for a relatively weak interaction between local precipitation and surface water in the systems supplying the water, consistent with the dominant use of groundwater or water from river basins with a relatively long residence time.…”
Section: Resultsmentioning
confidence: 95%